Corksorb Enhances Alkane Degradation by Hydrocarbonoclastic Bacteria - Martins, Valdo R.; Freitas, Carlos J. B.; Castro, A. Rita; Silva, Rita M.; Gudiña, Eduardo J.; Sequeira, João C.; Salvador, Andreia F.; Pereira, M. Alcina; Cavaleiro, Ana J. (Frontiers in Microbiology, 2021)
Biosorbent materials are effective in the removal of spilled oil from water, but their effect on hydrocarbonoclastic bacteria is not known. Here, we show that corksorb, a cork-based biosorbent, enhances growth and alkane degradation by Rhodoccocus opacus B4 (Ro) and Alcanivorax borkumensis SK2 (Ab). Ro and Ab degraded 96 ± 1 % and 72 ± 2 %, respectively, of a mixture of n-alkanes (2 g L-1), respectively, in the presence of corksorb. These values represent an increase of 6 % and 24 %, respectively, relatively to the assays without corksorb. The biosorbent also increased the growth of Ab by 51 %. However, no significant changes were detected on the expression of genes involved in alkane uptake and degradation in the presence of corksorb, relatively to the control without the biosorbent. Nevertheless, transcriptomics analysis revealed an increased expression of rRNA and tRNA coding genes, which confirms the higher metabolic activity of Ab in the presence of corksorb. The effect of corksorb is not related with the release of soluble stimulating compounds, but rather with the presence of the biosorbent, which was shown to be essential. Indeed, scanning electron microscopy images and down regulation of pili formation coding genes, which are involved in cell mobility, suggest that cells attachment on corksorb is determinant for the improved activity. Furthermore, the existence of native alkane-degrading bacteria in corksorb was revealed, which may assist in situ bioremediation. Hence, the use of corksorb in marine oil spills may induce a combined effect of sorption and stimulated biodegradation, with high potential for accelerating enhancing in situ bioremediation processes.